Exchange rate strategy in CARICOM : the way forward - Worrell, Delisle (2005)
Suggests that the introduction of a common currency in phases, beginning with the unification of the Trinidad and Tobago dollar, the Barbados dollar and the Eastern Caribbean dollar apprears feasible as a first stage of a monetary union within Caricom.